2017
DOI: 10.3892/mmr.2017.8310
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the neuroprotective effects of Lycium�barbarum water extract in apoptotic cells and Alzheimer's disease mice

Abstract: Alzheimer's disease (AD) affects people worldwide and is caused by chronic and progressive damage to the central nervous system. Lycium barbarum (LB), a renowned functional food and medicinal plant in Southeast Asia, may possess protective effects against nerve injury. The present study aimed to investigate the neuroprotective effects of LB water extract in a differentiated (D)PC12 cellular apoptosis model induced by L-glutamic acid (L-Glu), and a mouse model of AD, induced by the combination of AlCl3 and D-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Flow cytometry detection ( 10 ): i) the test objects were the fourth-generation BMSCs. ii) The centrifugation parameters for the preparation of the flow cytometry samples were 800 × g/min at 4°C for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry detection ( 10 ): i) the test objects were the fourth-generation BMSCs. ii) The centrifugation parameters for the preparation of the flow cytometry samples were 800 × g/min at 4°C for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Lycium barbarum (LB), a renowned functional food and medicinal plant in Southeast Asia. Research data suggested that LB may exert neuroprotective effects and may aid in preventing neurodegenerative disease [46]. According to TCM theory raised from thousands of years of clinical practice, compatibility of medicinal herbs can strengthen the therapeutic e cacy and attenuate the toxicity of major component through drug-drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Lycium barbarum has pharmacological actions such as regulating immunity, antitumor activity, nervous system function, liver protection, and slow aging process [185]. Hu et al [186] administered different doses of Chinese wolfberry, via the intragastric route, to a mouse model of AD induced by the combination of AlCl 3 and D-gal. They found that the quantity of horizontal and vertical movements increased while AChE and ChAT levels decreased significantly in mice.…”
Section: Lycium Barbarum (Gouqi)mentioning
confidence: 99%
“…Studies had shown that flavonoids had definite efficacy in the treatment of agerelated neurodegenerative diseases [226], cardiovascular diseases [227,228], atherosclerosis [229], etc. Some progress has Modulation of the mitochondrial pathway of apoptosis and the cholinergic system [186] 12…”
Section: Flavonoidsmentioning
confidence: 99%